Control of volunteer soybean in areas cultivated with Crotalaria spectabilis - Oliveira, Gustavo de Souza; Braz, Guilherme Braga Pereira; Almeida, Dieimisson Paulo; Procópio, Sergio de Oliveira; Filho, Silvio Vasconcelos de Paiva; Souza, Matheus de Freitas; Simon, Gustavo André (Revista de Ciências Agroveterinárias, 2023)
The presence of volunteer soybean plants in showy crotalaria (Crotalaria spectabilis) crops grown in the second crop has been common, thus necessitating the adoption of strategies for their management. The objective of this work was to evaluate the effectiveness and selectivity of the herbicides pyrithiobac-sodium and ethoxysulfuron applied isolated in post-emergence of showy crotalaria in order to control volunteer soybean. For this purpose, two field experiments were set up, one evaluating the feasibility of using the herbicide pyrithiobac-sodium and the other using ethoxysulfuron. In both experiments, a randomized completely block design was used, with treatments arranged in a 2x4+2 factorial scheme, with four replications. The first factor was allocated to the post-emergence application of herbicides at two distinct phenological stages V3 and 3 true leaves and V7 and 6 true leaves, respectively for soybean and showy crotalaria. In the second factor, increasing doses of herbicides were arranged, using doses 14.0; 22.4; 30.8; and 39.2 g ha-1 for pyrithiobac-sodium, and 18.0; 30.0; 42.0; and 54.0 g ha-1 for ethoxysulfuron. The additional treatments corresponded to an infested check and a weeded check. Visual control evaluations of volunteer soybean were carried out, as well as phytointoxication, stand, height and dry mass of shoots of showy crotalaria plants. According to the results obtained, pyrithiobac-sodium at a dose of 30.8 g ha-1, can be recommended for applications when volunteer soybean plants are in V3 and showy crotalaria plants with 3 true leaves, as well as the herbicide ethoxysulfuron in dose 18 g ha-1, can be recommended for applications when volunteer soybean plants are at V3 or V7 and showy crotalaria plants owns three true leaves. These two herbicides at the respective doses have the potential to be registered for use in areas where showy crotalaria is grown in succession to soybean crop.